Peripheral blood smear findings in a kidney transplant recipient with disseminated histoplasmosis and elevated Aspergillus galactomannan. Issue 4 (21st June 2019) - McCurdy, Lewis; Wheat, Lawrence Joseph; Block, Jared; Gajurel, Kiran
Abstract: We report a case of disseminated histoplasmosis in a renal transplant recipient who presented with a nodular pulmonary lesion and elevated serum and bronchoalveolar lavage (BAL) Aspergillus galatomannan. This almost led to an erroneous diagnosis of invasive aspergillosis since the donor respiratory tract was known to be colonized with Aspergillus terreus . However, distinctive intracelluar Histoplasma yeasts on peripheral blood smear led to early diagnosis and appropriate treatment. The cross‐reactivity between Aspergillus galactomannan and Histoplasma antigen is discussed further.